Accumulation and removal of Streptococcus mutans biofilm on enamel and root surfaces in vitro - Anne Breivik; Aida Mulic; Amer Sehic; Håkon Rukke Valen; Simen Kopperud; Linda Stein; Qalbi Khan (Medical Journals Sweden, 2024)
Objective: This study aimed to quantitatively investigate the accumulation of Streptococcus mutans biofilm on enamel and root surfaces and assess the amount of biofilm removal using (1) experimental toothpaste and (2) water, in a closed system of flow chamber. Methods: Eight sound premolars were embedded in epoxy resin and polished with silicon carbide grinding papers to display enamel and root surfaces. To mimic biofilm, cultures of Streptococcus mutans were prepared and grown on the tooth surfaces over night before they were exposed to either 2 liters of Milli Q water or 2 liters of 40% experimental toothpaste in the flow chamber. The amount of biofilm was measured and quantified in Fluorescence microscopy. Mean fluorescence values were recorded and analysed using Microsoft® Excel® (MS Excel 2016). Results: The ability to grow biofilm was equally present at both the enamel and root surfaces. The use of water and 40% experimental toothpaste showed a significant reduction of areas covered with biofilm on both enamel and root dentin in comparison to untreated surfaces (p < 0.01). Significantly more biofilm was removed from enamel compared to root surfaces when treated with either water and toothpaste (p < 0.01). Slightly less biofilm was removed by the use of water compared to toothpaste on both enamel and root dentin surfaces, although the differences were not statistically significant. Conclusion: The results indicate that less biofilm is removed from the root surfaces than enamel by the use of water and 40% experimental toothpaste in flow chamber. Assessing oral biofilm accumulation and monitoring biofilm formation on enamel and root dentin surfaces give oral health professionals important directions that could strenghten the significance of dental caries prevention. Improving older individuals' oral hygiene practices should therefore be considered an important measure to prevent root caries.